The Value of Serum Exosomal miR-184 in the Diagnosis of NSCLC. (11th April 2022) - Li, Shujun; Lin, Yanming; Wu, Yanxia; Chen, Hualin; Huang, Zhong; Lin, Muwen; Dong, Jiali; Wang, Yongcun; Yang, Zhixiong
Abstract : Lung cancer has the highest morbidity rate (11.6%) and mortality rate (18.4%) among all current tumors. The morbidity rate in China accounts for approximately one-third, and it is still rising. Nonsmall cell lung cancer is the most common type of lung cancer, accounting for 80%–85% of all lung cancers, and approximately 57% of patients with advanced nonsmall cell lung cancer have distant metastases at the time of diagnosis. To explore the expression changes in microRNA-184 (miR-184) and its clinical value in serum exosomes of patients with nonsmall cell lung cancer (NSCLC). This study adopted a case-control study method, selecting 88 patients (NSCLC group) from June 2015 to June 2017 in our hospital who are confirmed to have NSCLC by fiber-optic bronchoscopy, and 90 patients who are confirmed to have benign lung diseases by pathological examination during the same period (control group). Fluorescence quantitative PCR technology is used to detect the levels of miR-184 in serum exosomes of the two groups, and the differences in the levels of miR-184 in serum exosomes of NSCLC patients with different pathological characteristics are analyzed. According to the results of the 3-year follow-up, the miR-184 levels in serum exosomes of NSCLC patients are grouped and compared. The expression level of miR-184 in serum exosomes in the NSCLC group is significantly higher than that in the control group, and the difference between the two groups is statistically significant (p < 0.05). The ROC curve is drawn with the expression level of miR-184 in serum exosomes of the two groups of patients. The results showed that the area under the ROC curve for the differential diagnosis of NSCLC and benign lung tumors with the expression level of miR-184 in serum exosomes is 0.927, and the sensitivity is 87.61%, while the specificity is 84.02%. The expression levels of miR-184 in serum exosomes of NSCLC patients with different pathological characteristics, in different TNM stages [(I+II) vs. (III+IV)], lymph node metastasis (yes vs. no), and different degrees of differentiation [(High + Medium) vs. Poorly differentiated] are compared and showed statistical significance (p < 0.05). In 88 NSCLC patients, after 3 years of follow-up, 33 survived, and 55 died, with a survival rate of 37.50%. The expression of miR-184 in serum exosomes of the 33 surviving patients is significantly lower than that of the nonsurviving group (p < 0.05). The expression level of miR-184 in serum exosomes of NSCLC patients is significantly increased, which has a certain value for the differential diagnosis of the nature of benign and malignant lung diseases and is closely related to the prognosis of patients.